Pengaruh Metode Bermain Peran terhadap Perkembangan Sosial Emosional Anak Usia Dini di RA Qurrota A’yun Giritontro - Mulyani, Wiwik; Prahastiwi, Eka Danik (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on The influence of role-playing methods on the social and emotional development of early childhood, despite its significant impact on social emotional development of early childhood. The study aims to to determine the influence of children's social emotional development before and after using the role play method. Design, with a sample of [number of participants/cases/regions] selected through qualitative method with descriptive research type, with a sample of 20 children in group B at RA Qurrota A'yun Giritontro selected through purposive sampling. Data was collected using interviews, observations, documentation and analytical using regression analysis techniques. The findings reveal that the role play method has a positive relationship with the social emotional development of group B children at RA Qurrota A'yun Giritontro. This finding is in line with the research objectives and strengthens the humanistic theory (internal factors inherent in humans themselves) and the psychosocial theory (external factors, namely the surrounding environment). The study concludes that the importance of the role of the role-playing method in the social emotional development of children to foster self-confidence, curiosity and empathy in children in group B RA Qurrota A'yun Giritontro. The implications encompass theoretical contributions, such as advancing the literature on The influence of role-playing methods on the social and emotional development of early childhood, and practical recommendations for RA Qurrota A'yun Giritontro to be able to improve learning with the role-playing method once every two weeks with different role-playing themes to further hone children's social emotional abilities and to anticipate so that children do not get bored in the learning process. Additionally, this study identifies future research opportunities on The Effectiveness of Role Playing Methods on the Development of Children's Emotional Intelligence.